Thermo-catalytic reforming (Tcr®) in demonstration scale – experiences from scale up - Daschner, Robert; Apfelbacher, Andreas; Walberer, Julian; Hornung, Andreas (European Biomass Conference and Exhibition Proceedings, 2019)
Bioenergy will play a major role in the energy transition as we head towards a CO2-neutral energy system. Biogenic residues like sewage sludge, composting residues, paper residues etc. are various examples of residue streams available for innovative applications. E.g. in Germany more than 7500 anaerobic digestion plants generate about 60 million tons of digestate residues every year. For the conversion of such feedstocks, Fraunhofer UMSICHT developed the Thermo-Catalytic Reforming (TCR®) technology. Starting from a lab-scale TCR®-2 unit (2 kg*h-1), to a demo-scale TCR®30 plant (30 kg*h-1), the TCR® technology was scaled-up to a 300 kg*h-1 plant for the conversion of sewage sludge at an industrial rate. The plant can be used for power and heat production by combined heat and power application of the TCR® products oil and gas on a dual-fuel engine. Additionally, the produced biochar can be used for energy purposes, e.g. with gasification technology. Furthermore, the produced oil can be upgraded to biofuel on standard conditions (sustainable diesel referring to EN590 and sustainable petrol referring to EN228). First commissioning and test runs with sewage sludge at the premises of Fraunhofer UMSICHT showed that the scale up of the TCR®-technology from lab-scale to demo scale plant was successful. Analytics of the products of the pilot plant demonstrated the high quality of the products.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Biofuel; Biogenic residues; Industrial scale application; Pyrolysis; Thermo-chemical conversion; Up-scale